FEED BACK STRATEGY AS AN ALTERNATIVE LEARNING STRATEGY: IMPLEMENTATION AND CHALLENGE. - Eliza, Tiara (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2021)
Nowadays, the development of technology and learning system have been rapidly increasing and changing as the educators are challenged how to be creative in finding a new strategy in learning and teaching process. It will guide the students to get optimal progress in learning outcomes. There are various ways in learning strategies that are applied by the educators which usually they spend much time in designing high quality learning tasks, creating engaging activities and relentlessly pursuing better classroom routines and behavior management. All of these elements are considered in achieving learning outcomes while there is another essential element that the educators often do not plan for or evaluate. The essential element is a feedback. Therefore, this paper is intended to be one of the references in developing teaching learning strategies to achieve an optimal learning outcome in learning and teaching process. This studyused descriptive qualitative analysis. The result of this study indicates that the feedback strategy provides positive results in achieving learning goal and outcome.